2008
DOI: 10.1007/s10509-008-9773-z
|View full text |Cite
|
Sign up to set email alerts
|

Scalar field theory and energy-momentum problem of Yilmaz-Rosen metric in general relativity and teleparallel gravity

Abstract: In this paper, using the energy momentum definitions of the Einstein, Bergmann-Thomson, Landau-Lifshitz and Møller in general relativity (GR) and teleparallel gravity (TG), we have evaluated the energy-momentum distributions of Yilmaz-Rosen metric. We have obtained that these different energy-momentum definitions give different results in GR and TG. Furthermore these results are same in different gravitation theories and we get that both general relativity and teleparallel gravity are equivalent theories for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Also, they have shown that both the general relativity and the teleparallel gravity are equivalent [56]. Similar results have also been obtained by Aygün and coworkers in [57,58] where the authors have concluded that energy-momentum definitions are identical not only in general relavity but also in teleparallel gravity.…”
supporting
confidence: 76%
“…Also, they have shown that both the general relativity and the teleparallel gravity are equivalent [56]. Similar results have also been obtained by Aygün and coworkers in [57,58] where the authors have concluded that energy-momentum definitions are identical not only in general relavity but also in teleparallel gravity.…”
supporting
confidence: 76%
“…which also may be obtained from (54) by taking γ → ∞. Now, this final relation (60) may be compared with its Kerr-type "isotropic" analogue following directly from (56) by applying (13). Some results of this comparison of vacuum and antiscalar Lense-Thirring effects in strong-field regime (small r) are represented in Fig.…”
Section: Rotating Mass In the Antiscalar Backgroundmentioning
confidence: 99%
“…The issue of energy localization has also been considered in the framework of teleparallel gravity [44][45][46][47][48][49]. It has been concluded in some recent works that the energy-momentum definitions are identical not only in GR but also in teleparallel gravity [48,50,51].…”
Section: Introductionmentioning
confidence: 99%